Edukasi Multimedia Interaktif 5 Kunci Keamanan Pangan pada Siswa MI Muhammadiyah Kota Utara, Kota Gorontalo - Atikah Siti Warahma Lukum; Vidya Avianti Hadju (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Food safety is a crucial aspect of maintaining the health of elementary school students, particularly regarding snacking habits in school settings that carry a risk of food poisoning. This community service project aims to enhance the knowledge of third-grade students at MI Muhammadiyah in Kota Utara District, Gorontalo City, regarding the 5 Keys to Food Safety through interactive education. The method used was a one-group pretest-posttest design, with educational media such as posters, PowerPoint (PPT) presentations, songs, and educational games to make the material easier to understand and more engaging for the students. During the activity, the students demonstrated active participation and high enthusiasm. The evaluation results showed that the students’ average knowledge score increased from 6.07 to 8.70, representing a 43.33% improvement. The Wilcoxon test revealed a significant difference between the pretest and posttest scores (p=0.003), indicating the success of the educational intervention. These results demonstrate that interactive education is effective in improving elementary school students’ knowledge of food safety. This educational approach has the potential to serve as an alternative health promotion strategy that can be implemented sustainably in other schools.